A BIA-NOMA Scheme for Downlink of Two-Cell SISO Network. Issue 2 (April 2020) - Chen, Kaiping; Zhou, Qingfeng; Wang, Juan; Wu, Jianjian
Abstract: This paper studies a transmission problem based on a two-cell downlink SISO network. We propose a blind interference alignment transmission scheme based on TDMA by using interference alignment technology, which can improve the DoF of users. In order to improve the average achievable sum-rate of the system, we propose the BIA-NOMA scheme by combining NOMA with BIA technology. Theoretical analysis shows that the BIA-NOMA scheme can effectively improve the achievable rate of the center users, and its sum-rate is higher than that of the BIA-TDMA scheme. At the end of this paper, we give the simulation results to verify the performance of the scheme.